EFFECT OF FORTIFIED MILK (CALCIUM AND VITAMIN D) AND OSTEOPOROSIS GYMNASTICS TOWARD BONE DENSITY OF PRE ELDERLY WOMEN IN THE WORKING AREA OF HEALTH CENTER BANYUANYAR IN DISTRICT SAMPANG - Prasetya, Desy; Wirjatmadi, Bambang; Adriani, Merryana (Universitas Wijaya Kusuma Surabaya, 2015)
Disorders of bone density becomes a major public health problem, especially in women pre elderly. Besides due to low intake of essential nutrients for bone, also because of declining estrogen due to menopause. Low bone density can lead to osteoporosis and impact on risk of bone fracture. Fortified milk is one of strategy to provide the intake of calcium and vitamin D daily. In addition, osteoporosis gymnastics also plays a role to increase the absorption of calcium in the small intestine. The aim of this study was to analyzed the effect of fortified milk (calcium and vitamin D) and osteoporosis gymnastics on bone density in women pre elderly in the working area of health center Banyuanyar Sampang. Research design used Non equivalent Control Group Design. Samples were 45 pre elderly womens (age 50-59 years) which is composed of 15 people (treatment group I) in the form of gymnastics osteoporosis, 15 (treatment group II) in the form of osteoporosis gymnastics and fortified milk, and 15 people in the control group. Statistical test using paired T-test, Wilcoxon and Kolmogorov Smirnov. There was the influence of fortified milk (calcium and vitamin D) and osteoporosis gymnastics on bone density (p = 0.037). While in the first treatment group (p = 0.217) and showed no effect on controls groups (p = 0.157). There was the influence of fortified milk (calcium and vitamin D) and osteoporosis gymnastics on bone density. Some respondents have improvement or increase of T-score.